Low-Level Lead Exposure and Heart Rate Variability in Childhood: a Longitudinal Study - Tymchenko S.; Evstafyeva E. (E3S Web of Conferences, 2013)
The objective of the present study was to assess whether small elevations in lead level were associated with measurable changes in autonomic cardiovascular regulation in urban children between 10 and 13 years old (n=30). Examinations at ages 10-11, 11-12 and 12-13 years included heart rate variability (HRV) and its time and frequency components. And lead concentrations were determined in the child’s hair and based on its content children were considered to be leadexposed if their lead level was above 5 μg/g. Results show that both time-domain (SDNN, RMSSD, pNN50) and frequency-domain (TP, HF) HRV parameters increased by about 20% from 10 to 13 years (p<0.001). Number of leadexposed children also significantly increased and by the age of 12 half of the study group had lead levels above 5 μg/g. Content of lead in hair as biomarker of exposure was associated with a decrease in SDNN, TP, VLF, LF, LF/HF, LFn (p<0.05) at age 12-13 years in nonexposed group, indicating decreased sympathetic (LF) and parasympathetic (SDNN) modulation of the HRV, which may be caused by underlying lead neurotoxicity at the central levels.